THE PUNISHING WORD OF LOVE (Shevchenko’s gospel core) - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article expresses the idea of firmness of Taras Shevchenko’s personality in the spiritual life of Ukraine. On the occasion of the poet’s jubilee the emotional state of the soul is revealed.